Pemberdayaan UMKM Melalui Strategi Komunikasi Pembangunan: Studi Kasus Kukiv dan D'dimsum di Surabaya - Meiliya Wati; Marya Ulfa Hidayah; Calista Salsabila Azhari; Orinza Fajria; Veronika Sanctissima Apriani Mithe; Moh. Dey Prayogo (INDO PUBLISHING, 2026)
The empowerment of Micro, Small, and Medium Enterprises (MSMEs) has become one of the priorities in Indonesia's economic development in the digital transformation era. This Development Communication practicum aimed to empower two MSMEs in Surabaya, namely Kukiv and D'dimsum, through a participatory development communication approach. Kukiv is an MSME specializing in gluten-free products that required support in strengthening its digital content strategy, while D'dimsum, a newly established business, required promotional media to support its business introduction. The study employed the Participatory Action Research (PAR) method combined with a capacity-building approach and direct assistance. The results indicate that the assistance provided to Kukiv focused on planning and producing digital promotional content, whereas the assistance for D'dimsum included designing a promotional banner and producing three soft-selling videos that were published on the business's social media account. These findings demonstrate that development communication strategies tailored to the specific needs of each MSME can support the development of promotional media and strengthen business identity.